Evaluation of an instrumental method to reduce error in canopy water storage estimates via mechanical displacement. Issue 1 (10th January 2013) - Van, John T.; Martin, Kael; Friesen, Jan; Jarvis, Matthew T.; Lundquist, Jessica D.; Levia, Delphis F.
Key Points Evaluated method may allow removal of multidirectional bending strains Canopy water loading signal may be isolated using the evaluated method Sample storms show water loading response to rainfall until storage capacity